Ensuring Food Security in Indonesia: The Urgent Need for Food Loss and Waste Regulation - Baity, Sheila Noor; Afinnas, Muhamad Agil Aufa (Fakultas Hukum Universitas Islam Indonesia, 2025)
The phenomenon of Food Loss and Waste (FLW) is a problem with serious impacts on environmental, economic, and social aspects. This research aims to analyze the normative issues surrounding FLW in Indonesia in accordance with the mandate of Article 27 and 28H(1) of the 1945 Constitution, while also offering prescriptions on how Indonesian law should address the FLW issue. This research is a normative legal research, using a conceptual and comparative approach. The comparative approach involves analyzing legal systems in three jurisdictions: Europe, America, and Asia. Furthermore, the concept of smart regulation is used as a perspective to prescribe effective FLW regulations in Indonesia. The findings of this research show that Indonesia has demonstrated awareness of FLW through the National Food waste Agency (NFA), the legal draft on FLW and the revision of Food law in progress. However, the absence of specific regulations on FLW proves to be counterproductive to the current government priorities. Secondly, to address the FLW issue, a combination of Command and Control (CaC) instruments, economic instruments, and educational and informational strategies is highly recommended. Integrating these three instruments is expected to encourage all stakeholders—including the government, business actors, and the community—to contribute to solving the FLW problem. This recommendation is also supported by an analysis of FLW regulations in Europe, America, and Asia, which reveals that a combination of Command and Control (CaC) mechanisms, economic instruments, and education can effectively reduce FLW in these regions.